2007
DOI: 10.1002/cphc.200700170
|View full text |Cite
|
Sign up to set email alerts
|

A Dyadic Sensitizer for Dye Solar Cells with High Energy‐Transfer Efficiency in the Device

Abstract: A new bichromophoric dyad based on an alkyl-functionalized aminonaphthalimide as energy-donor chromophore and [Ru(dcbpy)2(acac)]Cl (dcbpy=4,4'-dicarboxybipyridine, acac=acetylacetonato) as energy acceptor and sensitizing chromophore is synthesized. Efficient quenching of the donor-chromophore emission is observed in solution, presumably due to resonant energy transfer. This dyad is then used as a sensitizer in a dye solar cell. By comparing the spectral properties of transparent dye solar cells sensitized with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 53 publications
2
62
0
1
Order By: Relevance
“…16 One of the studies was able to demonstrate high excitation transfer efficiency (>89%) between attached dye molecules and an improvement in the device external quantum efficiency of 5-10% between the 400 and 500 nm spectral range. However, the overall power conversion efficiency enhancement of the DSSC was low (<9%), and was argued to arise due to an increase in the open circuit voltage rather than an increase in the short-circuit photocurrent density.…”
Section: -1mentioning
confidence: 99%
“…16 One of the studies was able to demonstrate high excitation transfer efficiency (>89%) between attached dye molecules and an improvement in the device external quantum efficiency of 5-10% between the 400 and 500 nm spectral range. However, the overall power conversion efficiency enhancement of the DSSC was low (<9%), and was argued to arise due to an increase in the open circuit voltage rather than an increase in the short-circuit photocurrent density.…”
Section: -1mentioning
confidence: 99%
“…Energy relay dyes (ERDs) have been used previously to increase light harvesting in the blue portion of the solar spectrum. 18,19 Blue ERDs, which absorb high energy photons and undergo FRET to sensitizing dyes, can efficiently transfer energy when placed inside the electrolyte 18,20 or cosensitized 21 on nanocrystalline TiO 2 . Grimes et al recently demonstrated that ERDs unattached to the titania and slightly red-shifted relative to the sensitizing dye peak absorption were able to undergo FRET to the SD.…”
Section: Introductionmentioning
confidence: 99%
“…22 However, the low FRET radii (e.g., 1À4 nm) due to the poor overlap between ERD emission and SD absorption prevents efficient energy transfer from occurring when ERDs are placed inside the electrolyte. 23 For DSC systems where energy transfer is weak (i.e., FRET radii <4 nm), NIR-ERDs should be within the FRET radius of the SD to efficiently transfer energy, which requires tethering between dyes 19 or cosensitization on the TiO 2 surface. 21 …”
Section: Introductionmentioning
confidence: 99%
“…L ong range energy transfer has recently been used to increase light harvesting [1][2][3][4][5][6][7] inside of dye-sensitized solar cells (DSCs). [8][9][10][11] In one architecture, energy relay dyes (ERDs) absorb high-energy photons and transfer energy via Förster resonant energy transfer to the sensitizing dyes.…”
mentioning
confidence: 99%